2008
DOI: 10.1159/000117714
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Aryl Hydrocarbon Receptor (AhR) Induces Regression of the Seminal Vesicle in Aged Male Mice

Abstract: The aryl hydrocarbon receptor (AhR) is a ligand-activated transcription factor that mediates diverse dioxin toxicities. Despite mediating the adverse effects, the AhR gene is conserved among animal species, suggesting important physiological functions for AhR. In fact, a recent study revealed that AhR has an intrinsic function in female reproduction, though its role in male reproduction is largely unknown. In this study, we show age-dependent regression of the seminal vesicles, probably together with the coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 63 publications
2
32
3
Order By: Relevance
“…A previous study found that the loss of AhR causes reduced fertility in male mice and that regression of the seminal vesicles was responsible for this phenotype in the aged AhR −/− male mice (11). We found reduced fertility in young AhR −/− male mice measured by number of pups in a litter.…”
Section: Low Fertility Of Young Ahr-deficient Male Mice With No Changsupporting
confidence: 59%
See 1 more Smart Citation
“…A previous study found that the loss of AhR causes reduced fertility in male mice and that regression of the seminal vesicles was responsible for this phenotype in the aged AhR −/− male mice (11). We found reduced fertility in young AhR −/− male mice measured by number of pups in a litter.…”
Section: Low Fertility Of Young Ahr-deficient Male Mice With No Changsupporting
confidence: 59%
“…Previous studies on the role of AhR in reproduction in male mice revealed that seminal vesicles were regressed in the aged AhR −/− male mice (11). In the present study, we found no such regression in young or old AhR −/− male mice, but nonetheless fertility was reduced and there was marked growth of mammary ducts.…”
contrasting
confidence: 67%
“…Other mechanisms may involve altered hormonal signaling as developmental exposure to dioxins inhibit sex steroid biosynthesis by suppressing activity of testicular STAR protein [76]. Male mice with AhR knockout (AhR(−/−)) have impaired testosterone synthesis in Leydig cells and low sperm counts [77]. Furthermore, dioxin-activated AhR/ARNT can recruit estrogen receptor and co-activator p300 to estrogen-responsive elements (EREs), leading to transactivation and estrogenic effects in the absence of estrogenic ligand [78].…”
Section: Mechanisms Of Epigenetic Reprograming By Dioxinsmentioning
confidence: 99%
“…Common features of the AhR −/− mice are decreased liver size, hepatic portal fibrosis, and decreased constitutive expression of drug metabolizing enzymes such a P4501A1 and 1B1 (10). In the AhR mice produced in the Bradfield laboratory, seminal vesicle weight was higher than that of WT mice at postnatal day 35 (11), whereas in the AhR −/− mice produced in the Fujii-Kuriyama laboratory, seminal vesicles were reported to regress in an age-dependent manner (12). To date no abnormalities in the metabolism of purines or excretion of urate have been reported in AhR −/− mice and variable effects on the immune system have been reported in the three AhR −/− strains.…”
mentioning
confidence: 99%